Analysis of optical waveguide discontinuities using Denman‐Beavers iterative scheme. Issue 24 (1st November 2014) - Wu, Shengbao; Xiao, Jinbiao; Sun, Xiaohan
Abstract : A new approach for solving the optical waveguide discontinuity problems is proposed, where the field‐based operator techniques are employed. Instead of using Padé approximation, the square roots of the characteristic matrices are approximated by the Denman‐Beavers iterative scheme with a branch‐cut rotation in the complex plane. Numerical results show that the present scheme is more accurate and stable than the widely used Padé approximation.